Validity of the association between periodontitis and female infertility conditions: a concise review. Issue 3 (September 2020) - Machado, Vanessa; Lopes, Joana; Patrão, Mariana; Botelho, João; Proença, Luís; Mendes, José João
Abstract : Hormones and inflammatory mechanisms are implicated with female reproductive function, including follicle maturation, ovulation, embryo implantation, and pregnancy. Periodontitis is a chronic inflammatory disease due to a polymicrobial disruption of the homeostasis and may be considered as a potential risk factor that affect female fertility. The role of periodontitis is becoming meaningful, with significant associations with polycystic ovary syndrome, endometriosis and bacterial vaginosis. Further, periodontitis is linked with known risk factors towards female infertility, such as age, obesity, and chronic kidney disease. This review aims to summarize the available evidence on the association between periodontitis and female infertility-associated conditions, and to discuss warranting steps in future research.